Assessment of genetically modified maize 1507 × 59122 × MON810 × NK603 and subcombinations, for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2011‐92). (28th November 2017) - ,; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: In this opinion, the GMO Panel assessed the four‐event stack maize 1507 × 59122 ×  MON810 ×  NK603 and its ten subcombinations, independently of their origin. The GMO Panel previously assessed the four single events combined in this four‐event stack maize and five of their combinations and did not identify safety concerns. No new data on the single events or their previously assessed combinations leading to modification of the original conclusions were identified. Based on the molecular, agronomic, phenotypic and compositional characteristics, the combination of the single maize events and of the newly expressed proteins in the four‐event stack maize did not give rise to food and feed safety or nutritional issues. The GMO Panel concludes that the four‐event stack maize is as safe and as nutritious as its non‐GM comparator. In the case of accidental release of viable grains of maize 1507 × 59122 × MON810 × NK603 into the environment, this would not raise environmental safety concerns. For four of the subcombinations not previously assessed, protein expression data were provided and did not indicate an interaction affecting the levels of the newly expressed proteins in these subcombinations. The five subcombinations not previously assessed are expected to be as safe as the single maize events, the previously assessed subcombinations and the four‐event stack maize. The GMO Panel considers that post‐market monitoring of maize 1507 × 59122 ×MON810 × NK603 and its subcombinations is not necessary. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of maize 1507 × 59122 × MON810 ×NK603 and its subcombinations.